Inflammatory Markers During Early Treatment of Seroconverters in a Randomized Placebo-Controlled Trial of PrEP (ANRS-IPERGAY). (20th March 2021) - Chawki, Sylvain; Charreau, Isabelle; Gabassi, Audrey; Carette, Diane; Cua, Eric; Cotte, Laurent; Pialoux, Gilles; Pintado, Claire; Meyer, Laurence; Chaix, Marie-Laure; Delaugerre, Constance; Molina, Jean-Michel
Abstract: HIV-related inflammation is associated with poor outcomes. We describe inflammatory biomarkers in 17 participants in a pre-exposure prophylaxis trial who seroconverted with very early initiation of antiretroviral therapy. Inflammation peaked at the time of HIV infection and returned to baseline within 6–12 months. Starting antiretroviral therapy very early could help mitigate long-lasting HIV-related inflammation. Abstract : In seventeen HIV-seroconverters in a PrEP trial who were treated very early on, inflammation peaked at the time of HIV-infection and returned to pre-HIV-infection levels within twelve months. Starting antiretroviral therapy very early could help mitigate long-lasting HIV-related inflammation.